Assessment of the orthodontic knowledge demonstrated by dental school undergraduates: recognizing the key features of Angle Class II, Division 1 malocclusion - Cristiane Canavarro; José Augusto Mendes Miguel; Cátia Cardoso Abdo Quintão; Myrna de Faria Magalhães Torres; Juliana de Paiva Moura Ferreira; Ione Helena Vieira Portella Brunharo (Dental Press Editora, 2012)
OBJECTIVE: To investigate the ability of undergraduate students in diagnosing Angle Class II malocclusion and evaluate the clinical approach of these students toward a patient displaying this condition. METHODS: The sample consisted of 138 students attending the last semester of 10 dental schools in the State of Rio de Janeiro/Brazil assessed by questionnaires with closed questions. They were presented with photographs and dental casts of a patient in the mixed dentition, with Angle Class II malocclusion, increased overjet and overbite, deviated dental midlines and anterior diastemas in the upper arch. RESULTS: It was found that students easily identified increased overjet (92% of students), followed by the presence of diastemas (89%), midline deviation (84.7%) and increased overbite (77.3%). Conversely, approximately half the sample (n=70 or 51% of the students) were able to identify bilateral Angle Class II malocclusion. Nearly all agreed on the need for treatment and that it should be provided by a specialist (n=131 or 95%), but found it difficult to determine the ideal moment to start orthodontic treatment: 48.9% of the sample would begin treatment at the end of the mixed dentition, 41.7% would indicate treatment during deciduous dentition and 7.9% during permanent dentition. CONCLUSIONS: On completion of their undergraduate courses, students encounter difficulties in diagnosing Class II and even find it hard to articulate ideas about a basic treatment protocol to correct this malocclusion.